T2 Vitamin D Enhances Bronchial Epithelial Cell Antioxidant Responses And Reduces Their Pro-inflammatory Cytokine Response To Stimulation By Urban Particulate Matter. (10th November 2014) - Pfeffer, PE; Kelly, FJ; Hawrylowicz, CM
Abstract : Background: Particulate matter (PM) air pollution and vitamin D deficiency are environmental factors associated with asthma exacerbations and severe asthma. PM stimulates cellular inflammatory pathways through oxidative stress and vitamin D has been shown in other organ systems to protect against oxidative stress. We therefore investigated whether vitamin D might protect against PM-induced pro-inflammatory responses. Methods: Primary human bronchial epithelial cells (HBECs) were cultured with ambient PM and/or physiological concentrations of vitamin D. Production of pro-inflammatory cytokines was measured by multiplex bead array, gene transcription by microarray and oxidative stress with appropriate assays. Results: Addition of vitamin D significantly decreased production of IL-6 by PM-stimulated HBECs (p = 0.011), however, the reduction was greater in HBECs from healthy (n = 8) than from asthmatic (n = 7) donors (48.7% vs 28.0% reduction, p = 0.048). Gene transcription microarray identified a subset of pro-inflammatory cytokine genes all down-regulated by vitamin D including IL6, IL24, CXCL10 and CCL20 . Microarray also identified effects of vitamin D on antioxidant genes including G6PD (3.1 fold-induction with 1, 25(OH)D3, p < 0.001). G6PD encodes glucose-6 phosphate dehydrogenase, which is vital for production of reducing equivalents for antioxidant responses. Vitamin D significantly increased the cellular ratio of reduced to oxidised glutathione (1.6 fold-increase with 25(OH)D3, p = 0.042), enhancing the ability of cellular antioxidant pathways to protectively respond to oxidative stress. Furthermore, addition of vitamin D reduced levels of PM-stimulated 8-isoprostane (19.8% reduction, p = 0.045), a marker of oxidative stress damage. Inhibition of G6PD reduced the beneficial effect of vitamin D on PM-stimulated HBEC responses. Conclusion: Vitamin D beneficially modulates the response of human bronchial epithelial cells to pathological stimulation by PM, in part through enhancing antioxidant pathway responses. A reduction in PM-stimulated IL-6 is likely important given the association between PM, systemic inflammation and an IL-6 dependent coagulopathy in animal models. Furthermore, many of the vitamin D regulated mediators in the array have profound actions on the adaptive immune system. However, our research has also revealed the novel finding that cells from healthy and asthmatic individuals may respond differently to vitamin D.